2014
DOI: 10.1097/fjc.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NOX/VPO1 Pathway and Inflammatory Reaction by Trimethoxystilbene in Prevention of Cardiovascular Remodeling in Hypoxia-induced Pulmonary Hypertensive Rats

Abstract: Recent studies show that resveratrol exerts beneficial effects on prevention of pulmonary hypertension. This study is performed to explore the effects of trimethoxystilbene, a novel resveratrol analog, on rat pulmonary vascular remodeling and right ventricular hypertrophy in hypoxia-induced pulmonary arterial hypertension (PAH) and the underlying mechanisms. Sprague-Dawley rats were placed in a chamber and exposed to 10% O(2) continuously for 4 weeks to induce PAH. The effects of trimethoxystilbene (5 or 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Interestingly, some natural compounds exert therapeutic effect on PAH via targeting NOX. For example, a number of studies have reported that resveratrol was able to prevent the development of PAH through a mechanism involving a suppression of NOX [6]. As an active ingredient of S. miltiorrhiza, MLB attracts our special attention because its antioxidative effect is greater than that of α-lipoic acid, a super antioxidant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, some natural compounds exert therapeutic effect on PAH via targeting NOX. For example, a number of studies have reported that resveratrol was able to prevent the development of PAH through a mechanism involving a suppression of NOX [6]. As an active ingredient of S. miltiorrhiza, MLB attracts our special attention because its antioxidative effect is greater than that of α-lipoic acid, a super antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of PAH development, the RV adapts to the elevated pulmonary artery pressure by increasing its wall thickness and contractility. Besides the pressure overload, multiple factors including neurohumoral activation [5], oxidative stress [6], and inflammation [7] actually contribute a lot to the pathophysiology of RV remodeling in PAH. Among them, oxidative stress attracts intensive attention recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and in hypoxia‐induced rat model of pulmonary arterial hypertension (Liu et al . ). Our group has demonstrated that Cd activates JNK, Erk1/2, and p38 pathways via induction of ROS (Chen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, to improve oral bioavailability of RSV-specific complexes with liposomes, lipid or synthetic nanoparticles have been made, even if they resulted with low therapeutic potential [79,80]. In respiratory diseases reproduced in rodent like pulmonary hypertension, RSV ameliorates asthma and fibrosis via SIRT1 activation [81,82] and also its derivative, trimethoxystilbene, demonstrated antioxidant and anti-inflammatory properties in rats exposed to hypoxia [83]. Recently, Bastin and Djouadi [84] reviewed RSV potentiality against mitochondrial damage and myopathies, and promising results in an animal model of a fatal genetic disease called Duchenne muscular dystrophy were reported.…”
Section: Resveratrol and Its Derivatives As Sirtuin 1 Activators In Amentioning
confidence: 99%